Development of a test instrument using multiple representations to assess students understanding: A Rasch Model Analysis - Yayang Andita Putri; Faizah Qurrata Aini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Today's test instruments used in schools are still ineffective in assessing students' multi-representational understanding of the